Measuring Ultrasonic Characterisation to Determine the Impact of Toc and the Stress Field on Shale Gas Anisotropy - Altowairqi, Y.; Rezaee, M. Reza; Urosevic, Milovan; Delle Piane, C. (Australian Petroleum Production and Exploration Association, 2013)
While the majority of natural gas is produced from conventional sources, there is significant growth from unconventional sources, including shale-gas reservoirs. To produce gas economically, candidate shale typically requires a range of characteristics, including a relatively high total organic carbon (TOC) content, and it must be gas mature. Mechanical and dynamic elastic properties are also important shale characteristics that are not well understood as there have been a limited number of investigations of well-preserved samples. In this study, the elastic properties of shale samples are determined by measuring wave velocities. Arrays of ultrasonic transducers are used to measure five independent wave velocities, which are used to calculate the elastic properties of the shale. The results indicated that for the shale examined in this research, P- and S-wave velocities vary depending on the isotropic stress conditions with respect to the fabric and TOC content. It was shown that the isotropic stress significantly impacts velocity. In addition, S-wave anisotropy was significantly affected by increasing stress anisotropy. Stress orientation, with respect to fabric orientation, was found to be an important influence on the degree of anisotropy of the dynamic elastic properties in the shale. Furthermore, the relationship between acoustic impedance (AI) and TOC was established for all the samples.